Camelot [videorecording (DVD)] - Logan, Joshua; Harris, Richard, 1930-2002; Redgrave, Vanessa, 1937-; Nero, Franco; Lerner, Alan Jay, 1918-1986; White, T. H. (Terence Hanbury), 1906-1964 (Warner Home Video, 1998)
A musical interpretation of the legend of King Arthur.